Diatoms Versus Copepods: Could Frustule Traits Have a Role in Avoiding Predation? - Petrucciani, Alessandra; Chaerle, Peter; Norici, Alessandra (Frontiers in Marine Science, 2022)
Predation is one of the strongest selection pressures phytoplankton has evolved strategies to cope with. Concurrently, phytoplankton growth must deal with resource acquisition. Experiments on mono- and mixed cultures of morphologically different diatoms exposed to copepods were performed to assess if size and shape were primary drivers in avoiding predation. Additionally, frustule silicification was investigated as a potential factor affecting prey selection by copepods. Thalassiosira pseudonana, Conticribra weissflogii, Cylindrotheca closterium, and Phaeodactylum tricornutum were exposed to the presence of Temora longicornis, a calanoid copepod. The physiological response in terms of growth, elemental composition and morphology was determined. The power of Image Flow Cytometry allowed functional single-cell analyses of mixed cultures in the presence and absence of copepods. Results highlighted that T. pseudonana although the most eaten by copepods in monospecific cultures, was not the preferred prey when the bigger C. weissflogii was added to the culture. When pennates were co-cultured with centric diatoms, their growth was unaffected by predators. Our data suggested that the frustule morphology contributes to long-term prey-predator interaction since the elongated thinner frustule, which evolved more recently, benefited cells in escaping from predators also when facing competition for resources.